Treatment Outcomes of Infectious and Non-infectious Acute Exacerbation of Myositis-Related Interstitial Lung Disease - Lee, Hyun; Chung, Sung Jun; Kim, Sang Hyuk; Choi, Hayoung; Kim, Youlim; Park, Tai Sun; Park, Dong Won; Moon, Ji-Yong; Kim, Sang-Heon; Kim, Tae Hyung; Yoon, Ho Joo; Sohn, Jang Won (Frontiers in Medicine, 2022)
Introduction: Although respiratory infections are common causes of acute respiratory failure in patients with myositis-interstitial lung disease (ILD), limited data are available regarding the treatment outcomes by the etiologies of acute exacerbation (AE) of myositis-related ILD (infectious vs. non-infectious). Our study aimed to investigate the treatment outcomes of AE in patients with myositis-related ILD focused on the infectious etiology. Methods: A single center-based retrospective cohort was performed at Hanyang University Hospital from January 2000 to December 2018. A total of 36 patients with AE of myositis-related ILD were consecutively included. The exposure was etiologies of AE in myositis-related ILD, and the outcome was in-hospital mortality. The infectious etiology was defined as confirmation of bacteria, virus, or fungus in samples obtained from the respiratory tract. Results: Among the 36 patients, 17 were diagnosed with infectious AE. The overall in-hospital mortality rate of AE was 47.2%. Although the mortality rate in patients with infectious AE was lower (41.2%) than in those with non-infectious AE (52.6%), this difference was not statistically significant (p = 0.724). Survival analysis showed no significant difference in the mortality in patients with infectious AE and those with non-infectious AE (risk ratio 0.78, 95% confidence interval 0.38–1.59). Conclusion: Our study showed that infectious AE is an important cause of mortality in patients with myositis-related ILD, showing a similar risk of mortality of non-infectious AE.